e-FinLex (e-Financial Lexicon) - Nyandang, Joycelyne; Punding, Azlan Yusof; Pakasa, Umi Insyirah; Mejri, Norazimah (2025)
Finance involves the management of money and includes a variety of activities such as investing, borrowing, lending, budgeting, saving, and forecasting. It is generally categorized into three main areas: personal finance, corporate finance, and public or governmental finance. In today's world, two primary financial systems are in use: conventional finance, which follows traditional practices, and Islamic finance, which adheres to Shariah principles. Global market projections estimate that the financial services industry will grow to $33.54 trillion by 2024, marking a 7.7% increase from the previous year. With global GDP expected to reach $109.53 trillion in the same year, financial services would represent about 31% of the world economy. This substantial growth is driving expansion in the financial sector, both in terms of market scope and educational offerings. Many higher education institutions now provide finance-related programs. However, one of the common challenges faced by students is grasping and retaining the complex terminology used within financial systems. To address this, e-FinLex aims to support students by making it easier to learn and remember financial terms, eliminating the need to rely on bulky textbooks. This innovation is not limited to students; it is also beneficial for professionals, and anyone interested in gaining a better understanding of the banking and finance industry.